Pengaruh Ukuran Perusahaan, Leverage, dan Pertumbuhan Penjualan terhadap Manajemen Laba: Corporate Governance sebagai Pemoderasi - Rizky, Maraudin Hasmaru; Idawati, Wiwi (Media Ilmiah Akuntansi, 2024)
This study aims to examine and analyze the effect of the interaction of good corporate governance in moderating firm size, leverage, and sales growth on earnings management. The sample in this study is LQ-45 companies on the Indonesia Stock Exchange in the 2016- 2020 period. This study uses purposive sampling in selecting the sample to be used, obtained 33 companies as samples in the study. Therefore, the results of this study indicate that company size has a significant negative effect on earnings management of LQ--45 companies, leverage has a significant positive effect on earnings management of LQ-45 companies, sales growth has a significant positive effect on earnings management in LQ-45 companies in Indonesia. , good corporate governance cannot moderate the relationship between firm size and earnings management in LQ-45 companies, good corporate governance cannot moderate the relationship between leverage and earnings management in LQ-45 companies, good corporate governance cannot moderate the relationship between sales growth and earnings management in companies. LQ-45.